2020
DOI: 10.1007/s13399-020-00732-y
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline and co-digestion pretreatments: process optimization for enhancing the methane yield of Jatropha press cake

Abstract: Oil extraction and biodiesel production process produce a massive amount of by-products like Jatropha press cake (JPC) and crude glycerol (CG), which could be used as a potential substrate for methane production. However, the higher lignocellulosic and nitrogen content in the JPC act as a recalcitrant and inhibitor, respectivly, for microbes that are involved in the anaerobic digestion (AD) process. Therefore, the present study aimed to enhance the methane yield of JPC by optimizing the alkaline pretreatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
0
1
1
Order By: Relevance
“…Ewunie, Morken &Yigezu [24] showed that in the codigestion of JSC and crude glycerol by applying thermal Pretreatment processes and operating the fermenters in a mesophilic regime of 37°C, the methane yield increases by 40% to 353.90 mL g −1 VS compared to control; however, in the present investigation, the maximum methane yields were reached in the thermophilic regime (50°C) with 64% more CH4 production than the mesophilic regime (30°C). It should be noted that the values mentioned show favorable results with the use of cattle manure as a co-substrate for cultivation compared to other raw materials, with values of up to 60% more CH4 production.…”
Section: Discussioncontrasting
confidence: 60%
“…Ewunie, Morken &Yigezu [24] showed that in the codigestion of JSC and crude glycerol by applying thermal Pretreatment processes and operating the fermenters in a mesophilic regime of 37°C, the methane yield increases by 40% to 353.90 mL g −1 VS compared to control; however, in the present investigation, the maximum methane yields were reached in the thermophilic regime (50°C) with 64% more CH4 production than the mesophilic regime (30°C). It should be noted that the values mentioned show favorable results with the use of cattle manure as a co-substrate for cultivation compared to other raw materials, with values of up to 60% more CH4 production.…”
Section: Discussioncontrasting
confidence: 60%
“…Environmental and economic considerations indicated that co-digesting jatropha cake with crude glycerol was a better alternative than steam explosion for improving the methane yield. In another study, the same group assessed the effect of alkaline pretreatment and co-digestion with crude glycerol for improving AD of jatropha cake [169]. Alkaline pretreatment was relatively more effective than co-digestion with glycerol, but both methods resulted in higher methane yields than the AD of untreated cake.…”
Section: Steam Explosion Jatropha Press Cakementioning
confidence: 99%